Coronary microvascular function and myocardial fibrosis in women with angina pectoris and no obstructive coronary artery disease: the iPOWER study. Issue 1 (January 2017) - Mygind, Naja; Michelsen, Marie; Pena, Adam; Qayyum, Abbas; Frestad, Daria; Christensen, Thomas; Ghotbi, Adam; Dose, Nynne; Faber, Rebekka; Vejlstrup, Niels; Hasbak, Philip; Kjaer, Andreas; et al.
Abstract Background Even in absence of obstructive coronary artery disease women with angina pectoris have a poor prognosis possibly due to coronary microvascular disease. Coronary microvascular disease can be assessed by transthoracic Doppler echocardiography measuring coronary flow velocity reserve (CFVR) and by positron emission tomography measuring myocardial blood flow reserve (MBFR). Diffuse myocardial fibrosis can be assessed by cardiovascular magnetic resonance (CMR) T1 mapping. We hypothesized that coronary microvascular disease is associated with diffuse myocardial fibrosis. Methods Women with angina, a clinically indicated coronary angiogram with <50 % stenosis and no diabetes were included. CFVR was measured using dipyridamole (0.84 mg/kg) and MBFR using adenosine (0.84 mg/kg). Focal fibrosis was assessed by 1.5 T CMR late gadolinium enhancement (0.1 mmol/kg) and diffuse myocardial fibrosis by T1 mapping using a modified Look-Locker pulse sequence measuring T1 and extracellular volume fraction (ECV). Results CFVR and CMR were performed in 64 women, mean (SD) age 62.5 (8.3) years. MBFR was performed in a subgroup of 54 (84 %) of these women. Mean native T1 was 1023 (86) and ECV (%) was 33.7 (3.5); none had focal fibrosis. Median (IQR) CFVR was 2.3 (1.9; 2.7), 23 (36 %) had CFVR < 2 indicating coronary microvascular disease, and median MBFR was 2.7 (2.2; 3.0) and 19 (35 %) had a MBFR value below 2.5. No significant correlations were found between CFVR and ECV or native T1 (R 2  = 0.02;p  = 0.27 andR 2  = 0.004;p  = 0.61, respectively). There were also no correlations between MBFR and ECV or native T1 (R 2  = 0.1;p  = 0.13 andR 2  = 0.004, p  = 0.64, respectively). CFVR and MBFR were correlated to hypertension and heart rate. Conclusion In women with angina and no obstructive coronary artery disease we found no association between measures of coronary microvascular disease and myocardial fibrosis, suggesting that myocardial ischemia induced by coronary microvascular disease does not elicit myocardial fibrosis in this population. The examined parameters seem to provide independent information about myocardial and coronary disease.